Efficacy and safety of agents for IgA nephropathy: a network meta-analysis of randomized controlled trials - Chen, Bo; Zhu, Yan; Yang, Yang; Xu, Gaosi (Frontiers in Medicine, 2025)
ObjectiveIgA nephropathy (IgAN) is the leading cause of end-stage renal disease (ESRD) globally, with its pathological mechanisms closely related to mucosal immune abnormalities and complement activation. Currently, there is no curative treatment. This study aims to systematically evaluate the efficacy differences of existing treatment regimens on clinical remission (CR), 24-h urinary protein excretion (24-h UPE), ESRD or kidney damage (KD) and adverse events (AEs) in IgAN, providing evidence-based support for optimizing stratified treatment strategies.MethodsA systematic search was conducted in the PubMed, Web of Science, Embase, and Cochrane Library databases up to February 20, 2025, including 57 randomized controlled trials (RCTs) covering 19 interventions. Pairwise and network meta-analyses were employed to assess binary variable (CR, ESRD or KD, AEs) using risk ratios (RR) and continuous variable (24-h UPE) using standardized mean differences (SMD), with interventions ranked based on the area under the cumulative ranking curve.ResultsClinical remission (26 RCTs included in the analysis): The CR for tonsillectomy combined with steroids pulse therapy (TSP) (RR = 8.23, 95% CI 4.11–16.45), anti-APRIL monoclonal antibody sibeprenlimab (RR = 10.00, 1.34–74.48), and steroids combined with renin-angiotensin system inhibitors (STE + RASI) (RR = 5.03, 2.61–9.68) were significantly superior to placebo. Proteinuria control (36 studies assessing 24-h UPE): The BLyS/APRIL dual-target inhibitor telitacicept (SMD = −5.21, −7.55 to −2.87) and STE + RASI (SMD = −1.98, −3.15 to −0.82) significantly reduced 24-h UPE, outperforming the mycophenolate mofetil combined with steroids regimen (SMD = −0.97, −2.74 to 0.80). Renal endpoint events (26 studies analyzing ESKD or KD): STE + RASI reduced the risk of ESKD or KD by 98.1% (optimal SUCRA ranking), followed by the dual endothelin/angiotensin receptor antagonist sparsentan (82.6%). Safety (36 studies reporting adverse events): The complement inhibitor iptacopan (88.4%) and sodium-glucose co-transporter 2 inhibitors (SGLT2i) (85.4%) had the lowest incidence of adverse events, significantly better than immunosuppressive regimens.ConclusionSTE + RASI serves as a core therapeutic strategy for IgAN, significantly improving clinical remission rates, reducing the risk of ESRD or KD, and addressing proteinuria. Telitacicept, sparsentan, and TSP can be considered as enhanced options for specific phenotypic patients, while targeted ileal budesonide (Nefecon) has not demonstrated a significant renal protective advantage.Systematic review registrationCRD42023494801.